Efecto de la temperatura y concentración de panela en la osmodeshidratación de camote (Ipomoea batata L.) asistido por ultrasonido y agitación - Rodríguez Diaz, Elda Yaselit (2019)
The objective of this research was to evaluate the effect of the temperature (30 – 60 °C) and concentration of brown sugar (30 – 60 % p/p) on the diffusivity coefficient of water and solids in sweet potato osmodehydration (Ipomoea batata L.) yellow variety. For this, a 2k + 2 (k) + 3 central points factorial statistical design was established, subjecting the samples to ultrasound treatments, agitation and a control. The results showed a maximum water loss of 54.42, 32.55 and 25.86 % in the treatments with ultrasound, agitation and no movement (control) respectively while the maximum gain of solids for the same treatments was 18.31, 11.21 and 9.01% respectively. As for the effective diffusivity, effective diffusivity coefficients for water and solids were obtained, respectively, between 3.22 – 6.05 x 10-10 m2/s and between 1.59 – 2.65 x 10-10 m2/s in the ultrasound treatment, between 2.31 – 4.24 x 10-10 m2/s and between 1.24 – 2.19 x 10-10 m2/s for treatment with agitation and between 1.50 – 2.71 x 10-10 m2/s and between 1.08 – 1.81 x 10-10 m2/s for treatment witness. The analysis of variance, indicates that there is significant influence (p > 0.05) by the independent variables (temperature and concentration of panela) analyzed, both linearly and quadratically, on the average diffusivity coefficient for water and solids both in the treatment with ultrasound, agitation and control. The analysis of variance showed a statistically significant effect (p < 0.05 and R2 ≈ 1) on the part of all the variables analyzed both linearly, quadratically and interactively. In the ultrasound treatment an optimum of panela between 45 – 50% w/w and temperature between 53 – 60 °C was obtained, for the treatment with agitation (100 rpm) an optimum of panela between 47 – 53% w/w was obtained temperature between 43 – 49 °C and for the ultrasound treatment (40 kHz), the optimum panela was between 53 – 57% w/w and the temperature between 47 – 51 °C.